TAJIKS OF THE FERGANA VALLEY AND THEIR ETHNO-DEMOGRAPHIC AND ETHNOLINGUISTIC CHARACTERISTICS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Tajiks are one of the oldest ethnic groups in Central Asia, including the Ferghana Valley. They are mainly located in the western and north-western part of the valley. Tajiks make up the majority of the population in the territory of the current Sogd region of Tajikistan. At the same time, in other regions of the Fergana valley, in particular, in Chust, Kosonsoy of the Namangan region, in a number of settlements in the Rishton, Fergana, Sokh districts of the Fergana region, the majority of the population are Tajiks.